Enacting the Code by effective national laws influence trends in exclusive breastfeeding: An analytical study from the Eastern Mediterranean Region - Ayoub Al-Jawaldeh; Azza Abul-Fadl; Nadia Fouad Farghaly (Indian Journal of Child Health, 2021)
Introduction: The marketing of breast milk substitutes (MBMSs) is presumed to be associated with declines in breastfeeding practices. National laws to control the MBMS are expected to improve exclusive breastfeeding (EBF) and continued breastfeeding (CBF) rates. Aim: This study aims to study the effect of national laws that control MBMS on EBF and CBF trends in the Eastern Mediterranean Region (EMR) countries. Methods: EMR infant feeding data for EBF and CBF were derived from the Global Database of the United Nations International Children’s Emergency Fund/World Health Organization (WHO). Data for the code of MBMS came from the WHO report in 2020. Percent change in EBF and CBF over the past 3 decades was correlated with scores given to the national laws according to their coverage of the provisions under the code. Results: Percent change in EBF correlated significantly with the total score given to national laws (r0.8; p